Penerapan Akad Wadi’ah Pada Produk Giro Di Bank Mega Syariah Kantor Cabang (KC) Malang - Moch. Novi Rifa’i, Putri Zakiatul Immamah & (Falah: Jurnal Ekonomi Syariah, 2017)
This article aims to know how the application of wadiah contract on the current account in the bank, and what are the current product and how to withdraw it. To conduct this research selected Bank Mega Syariah KC Malang as the object of research. Bank Mega Syariah is also a subsidiary of PT Mega Corpora which is under CT Corpora, one of the largest multinational companies in Indonesia that oversees nearly 30 companies. Based on research conducted, can be concluded that Bank Mega Syariah used wadiah contract on Giro products due to be taken by the customer at any time. Because if using mudharabah contract the customer can not take at any time, and must at maturity. Furthermore, by using wadiah contract, the bank can not register a demand deposit account in the program. In the wadiah contract is not known for profit or loss sharing, yet there is a bonus. There are two ways of take giro; first, by using check or transfer form (bilyet giro). If the Bank is designated in check or transfer form with the same bank account, the withdrawal may be directly at the bank’s counter. Second, if the intended bank in the check or transfer form is in different bank account, then the mechanism of clearing is done first.